HMGA proteins as modulators of chromatin structure during transcriptional activation - Ozturk, Nihan; Singh, Indrabahadur; Mehta, Aditi; Braun, Thomas; Barreto, Guillermo (Frontiers in Cell and Developmental Biology, 2014)
High mobility group (HMG) proteins are the most abundant non-histone chromatin associated proteins. HMG proteins bind to DNA and nucleosome and alter the structure of chromatin locally and globally. Accessibility to DNA within chromatin is a central factor that affects DNA-dependent nuclear processes such as transcription, replication, recombination and repair. HMG proteins associate with different multi-protein complexes to regulate these processes by mediating accessibility to DNA. HMG proteins can be subdivided into three families: HMGA, HMGB and HMGN. In this review, we will focus on recent advances in understanding the function of HMGA family members, specifically their role in gene transcription regulation during development and cancer.